Work Motivation and Workplace Environment as Determinants of Employee Satisfaction: A Quantitative Approach - Sasongko, Totok Aris; Handrito, Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the influence of the physical and non-physical workplace environment and work motivation on employee job satisfaction at CV Hages Jaya Barokah.   Design/Methodology/Approach – This study employs a quantitative research design using non-parametric statistical analysis. Data were collected from all 44 employees of CV Hages Jaya Barokah through a saturated sampling technique. Research instruments were tested for validity and reliability, while data were analyzed using Kendall's correlation analysis and the Mann–Whitney test with SPSS version 25.   Findings – The results indicate that the non-physical workplace environment has a positive and significant effect on employee job satisfaction. Work motivation also has a positive and significant effect on job satisfaction. Furthermore, the workplace environment and work motivation simultaneously have a significant influence on employee job satisfaction. These findings suggest that fostering supportive interpersonal relationships, organizational climate, and employee motivation can effectively enhance job satisfaction in small and medium enterprises.   Originality/Value – This research is original in utilizing non-parametric statistical methods to examine job satisfaction determinants within a local company setting. The findings provide practical value by offering evidence-based recommendations for improving the non-physical work environment and employee motivation.